Odpowiedzi

2009-12-13T19:08:47+01:00
I
4a-2=b
3a+7b=1,5

3a + 7(4a-2) = 1,5
b = 4a - 2

3a + 28a - 14 = 1,5
b = 4a - 2

31a = 15,5
b = 4a - 2

a = 15,5 / 31 = 1/2
b = 4* (1/2) - 2 = 2 - 2 = 0

a = 1/2
b = 0


II
6x-3y=9 | /3
x+5y=-9,5

2x - y = 3
x + 5y = -9,5

2x - 3 = y
x + 5(2x - 3) = -9,5

y = 2x - 3
x + 10x - 15 = -9,5

y = 2x - 3
11x = 5,5

y = 2x - 3
x = 5,5 / 11 = 1/2

y = 2*(1/2) - 3 = 1 - 3 = -2
x = 1/2

x = 1/2
y = -2
4 5 4
2009-12-13T19:09:55+01:00
I
4a-2=b
3a+7b=1,5

4a-2=b
3a+7(4a-2)=1,5

4a-2=b
3a+28a-14=1,5

4a-2=b
31a=15,5

b=0
a=0,5

II
6x-3y=9
x+5y=-9,5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9 /:3
x=-9,5-5y

-19-10y-y=3
x=-9,5-5y

-11y=22
x=9,5-5y

y=-2
x=19,5



2009-12-13T23:50:46+01:00
I
4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=1,5+14

b=4a-2
31a=15,5 /:31

b=4a-2
a=0,5

b=4*(0,5)-2
a=0,5

b=2-2
a=0,5

b=0
a=0,5




II
6x-3y=9
x+5y=-9,5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9
x=-9,5-5y

-57-30y-3y=9
x=-9,5-5y

-33y=9+57
x=-9,5-5y

-33y=66 /:(-33)
x=-9,5-5y

y=-2
x=-9,5 - 5*(-2)

x=-2
y=-9,5+10

x=-2
y=0,5

POZDRAWIAM :)